Study of Sea Grapes Seaweed (Caulerpa lentillifera J. Agardh) Production by Using Vermicompost Extracts in Closed Culture System - Pimolrat , Pornpimol; Saetan, Natthaphon; Sriyasak, Patcharawalai; Suwanpakdee , Supannee (Burapha Science Journal, 2026)
The purpose of this experiment was to study the results of the vermicompost extracts on the production of sea grapes seaweed (Caulerpa lentillifera J. Agardh) in closed culture system to produce safe food. The experiments were divided into two experiments. The first experiment was to investigate the effect of different fertilizers on the growth of seaweed in the closed system with a light intensity of 3,000 Lux. The experimental design used in this study was 4 treatments and 3 replications. These four treatments were seawater experiment set (control unit), adding vermicompost extracts, adding urea, and adding vermicompost extracts together with urea. C. lentillifera was trialed with the initial weight starting at 200 g and thallus length starting at 3 cm in the salinity of seawater of 30-35 part per thousand for the total period of 8 weeks. The results showed that the seaweed in the vermicompost extracts together with urea produced the highest increasing yield (average weight of 405.33±4.16 g and thallus length of 8.58±0.02 cm), significantly different (p <0.05) with the other experiments. The second experiment was to investigate the growth of seaweed cultured with vermicompost extracts with urea in the close system with different density consisted of: 200 (control), 300, 400 and 600 g of the initial weight per 15 liters of seawater for the total period of 8 weeks. The results showed that the initial weight starting at 200 g (control) yielded the highest average weight gain and thallus length. Weight gain reported for 104.6 percent of the initial weight. Therefore, culturing 200 g of the seaweed in a closed system with vermicompost extracts together with urea in 15 liters of seawater should be another option for culturing this seaweed in order to solve the problems caused by the climate change, especially in the rainy season. That can change the salinity of seawater and affect the production of the seaweed (C.lentillifera J. Agardh) continuously.